(untitled) - Alistair McMonnies (London, 1995)
Introduction to object-oriented programming; Introduction to abstract data types; Creating data structures using VDM and C++; Object modelling and case study.
Keywords: C (computer program language),Data structures (computer science),Object-oriented programming (computer science)